Pulmonary Metastases from an Undifferentiated Embryonal Sarcoma of the Liver: A Case Report and Review. (4th September 2018) - Shi, Mingxia; Xu, Hongzhi; Sangster, Guillermo P.; Gu, Xin
Abstract : Undifferentiated embryonal sarcoma of the liver (UESL) is a rare malignant hepatic tumor that occurs primarily in children. Only a limited number of cases have been reported in the literature due to low incidence of one per million, and reports of metastatic lesion of UESL are even rarer. We hereby describe the case of a 13-year-old male who presented with a palpable mass with imaging findings suggestive of a large complex tumor in the right lobe of the liver. He underwent extended right hepatectomy followed by adjuvant chemotherapy. The tumor was confirmed to be UESL by postoperative pathology and immunohistochemical staining analysis. Four years later, surveillance imaging revealed a small lung nodule in the left lower lobe. Complete removal of the lung tumor by wedge resection was performed, and a histological diagnosis of metastatic UESL was made. The patient also received postoperative adjuvant chemotherapy and is currently in a good general condition and tumor-free in the present eight-month period. This case is presented with emphasis on clinicopathological and immunohistochemical findings of the primary UESL and lung metastases with the aim of collecting more data and expanding our understanding of this rare malignancy.